Perception of Medical Students Regarding Implementing Telemedicine Practice Activities at a University Center in Brazil - Ponte, Clarisse Mourão Melo; Lopes, Laura da Silva Girão; Castelo, Maria Helane Costa Gurgel; Farias, Ludmilla Aline Guimarães Moreira; Lima, Maria Regina Cardoso Linhares Oliveira; Macedo, Maria Helena dos Santos; Sena, Idna Lara Goes de; Perdigão, Anne Caroline Bezerra; Pinheiro, Emanuel de Araújo; Kubrusly, Marcos (Journal of Health & Biological Sciences, 2024)
Objective: evaluate medical students' perceptions regarding implementing Telemedicine teaching during their undergraduate studies. Methods: this is a cross-sectional qualitative study with 30 medical students. Three focus group sessions were conducted, and the data were analyzed using a content analysis approach. Results/Discussion: the students recognized the importance of digital health strategies and digital information and communication technologies (ICTs) for the healthcare ecosystem. However, some students pointed out that this area is still challenging for some doctors who oppose Telemedicine. They reported a need for training professionals and students, emphasizing the need to improve skills and competencies for teleconsultation and other Telemedicine modalities. They stated that these experiences helped them enhance their empathy skills for establishing a good doctor-patient relationship. When referring to the negative aspects of the experiences, they mentioned the dependence on reliable internet connection and digital tools. Another limitation mentioned was the difficulty in conducting specific physical examination components. Conclusions: the students experienced Telemedicine activities in a safe healthcare environment, learning about the bioethical principles for responsible teleconsultations, understanding the limiting factors of the method, and having the opportunity to improve skills and competencies for their future professional practice.